Expanding extension - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
workshop hosted by the World Bank, with the collaboration of the International Federation of Agricultural Producers. It was held in Washington from 28 to 30 June 1999